Application of a methodology for retouching - Ana Bailão (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Between November 2006 and January 2010, an investigation into retouching methodologies was carried out. The aim of this paper is to describe, in four steps, the retouching methodology of a contemporary painting. The four steps are: chromatic and formal study, considering the use of Gestalt theory and the phenomena of contrast and assimilation; selection of the technique; choice of the materials and retouching practice.